Kegiatan Digital Poster & Video Competition - Dwi Pratiwi Wulandari; Nidia Wulansari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The video and poster competition is a follow-up to the Memorandum of Agreement (MoA) in Community Service between the Tourism Education Study Program at Indonesia University of Education (UPI) and the Tourism Study Program at Padang State University (UNP). The aim of this activity is to educate and promote sustainable tourism in the era of Society 5.0, involving active students from Vocational High Schools (SMK) in Tourism from West Java and the Greater Jakarta area. This activity is designed to turn students into agents of change in raising awareness about the importance of environmentally friendly tourism practices and supporting the sustainability of local culture. Through this competition, participants' creativity in producing promotional videos and digital posters demonstrates a significant improvement in their understanding of sustainable tourism concepts. Additionally, this activity fosters cross-sector collaboration with academics, tourism practitioners, and local governments. Thus, this initiative not only advances sustainable tourism education but also enhances innovation in the use of digital technology to convey environmental and cultural messages. This serves as an essential foundation for sustainable tourism efforts in Indonesia.